2014
DOI: 10.3201/eid2001.130531
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Pseudorabies Virus, China, 2012

Abstract: In 2012, an unprecedented large-scale outbreak of disease in pigs in China caused great economic losses to the swine industry. Isolates from pseudorabies virus epidemics in swine herds were characterized. Evidence confirmed that the pathogenic pseudorabies virus was the etiologic agent of this epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
128
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(138 citation statements)
references
References 11 publications
6
128
1
2
Order By: Relevance
“…PrV is the etiological agent of Aujeszky's disease, causing neurological, respiratory, and reproductive disease in the pig, its natural host. Despite successful vaccination campaigns and eradication of the virus from various countries, pseudorabies outbreaks still occur in swine populations worldwide, as recently reported from China (3). Because latent infection persists for lifetime after recovery from acute disease, pigs latently infected by PrV are a constant danger for virus reactivation, shedding, and spread in susceptible populations (4)(5)(6).…”
mentioning
confidence: 99%
“…PrV is the etiological agent of Aujeszky's disease, causing neurological, respiratory, and reproductive disease in the pig, its natural host. Despite successful vaccination campaigns and eradication of the virus from various countries, pseudorabies outbreaks still occur in swine populations worldwide, as recently reported from China (3). Because latent infection persists for lifetime after recovery from acute disease, pigs latently infected by PrV are a constant danger for virus reactivation, shedding, and spread in susceptible populations (4)(5)(6).…”
mentioning
confidence: 99%
“…This suggested that the PR vaccine was not effective against wild-type PR infection. According to recent studies, the causative agent of the outbreak was a PRV variant that showed enhanced pathogenicity [3,7,8,10]. In the present study, the PRV strain SH2012 was isolated in 2012 from an infected pig farm in Shanghai, China that used the typical vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The causative agent of the outbreaks was confirmed to be a PRV variant [3,9]. The PRV variant was shown to be both antigenically different from the classical PRVs and more pathogenic in older pigs [3,7,8,10]. Previous studies on immunological protection in sheep have shown that the Bartha-K61 vaccine does not provide complete protection against the emerging PRV variant, but could offer full protection against infection with PRV strain SC (an earlier virulent strain in China) [3,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The variant PRV primarily jeopardized pregnant sows and suckling piglets. Of the pregnant sows at a gestational age of 70-90 days, 5-35% experienced spontaneous abortion, 19 while the surviving piglets mainly exhibited anorexia, hydrostomia, vomiting, diarrhea, tremor, and posterior paralysis. The PRV gE gene was detected in clinical samples obtained from pigs from 15 farms in 6 provinces by specific PCR, and analysis of the gE gene sequence showed that all isolates belonged to a relatively independent cluster and contained 2 amino acid insertions.…”
Section: Research-article2015mentioning
confidence: 99%